"All out of print": modernism, minor forms, and Susan Miles's anachronistic late style. Issue 1 (2nd January 2020) - Preus, Anna
ABSTRACT: Susan Miles was a British poet, novelist, women's rights activist, and member of Bloomsbury literary circles from the 1910s through the 1930s. While she received some recognition for her poetry early in her career, she did not achieve long-term success, and she has largely been forgotten in discussions of modernist literature. At the age of seventy she published Lettice Delmer, a novel in verse that looks back on the high period of modernist literary production in England in the early twentieth century. Positioning this verse novel as an example of women's late style, I examine Miles's critique of the publishing institutions and literary culture that marginalized her work during her youth. Lettice Delmer exposes the way literary movements coalesce around shared aesthetic values and illustrates the costs particularly for those women authors whose writing was not easily integrated into avant-garde definitions of "new" literary form in the modernist period. I argue that Miles uses the hybrid verse novel as a bold critique of modernist literary production, which also simultaneously enacts a challenging late style that extends from the narrative itself into Miles's act of publishing the book despite her own obscurity and a relative lack of support for the project.